AB0074 Thrombospondin-1: a novel chondroitin sulfate target for osteoarthritis treatment. (23rd January 2014) - Calamia, V.; Lourido, L.; Mateos, J.; Fernandez-Puente, P.; Rocha, B.; Fernandez-Costa, C.; Montell, E.; Vergés, J.; Ruiz-Romero, C.; Blanco, F. J.
Abstract : Background: Recent works by our group provide evidences of the usefulness of proteomics techniques for anti-osteoarthritis (OA) drug screening [1 -3 ]. Objectives: The aim of this study is to identify protein markers for monitoring chondroitin sulfate (CS) treatment by OA chondrocytes secretome analysis using a quantitative proteomic approach (iTRAQ). Methods: Human articular chondrocytes (HACs) released from three OA cartilages were cultured in DMEM supplemented with antibiotics and 10% FBS. At confluence, OA chondrocytes were treated with 200 µg/mL of CS (100% purity, bovine origin). 48 hours later, conditioned media were collected and their proteins were concentrated and quantified. Trypsin digestion and labeling with isobaric tags using iTRAQ reagents were performed. Then, peptides from the two conditions (untreated and CS-treated) were mixed, separated by reversed-phase liquid chromatography (LC) and analyzed by nanoscale reversed-phase LC coupled to mass spectrometry (nLC-MALDI-MS/MS). The identification and quantification of proteins (by calculating the different iTRAQ tag intensities for each peptide) was carried out with Protein Pilot 4.0 software. Real-time, western blotting, and immunohistochemistry analyses were performed to validate the proteomics results. Results: Database search (UniprotKB/Swissprot) allowed us to identify 260 different proteins secreted by OA chondrocytes. Among them, we found 23 proteins differentially expressed between treated and untreated samples: 13 were increased by CS treatment and 10 were decreased. We considered only those proteins with a probability score higher than 95%, a ratio ≥1.3 or ≤-1.3, a p value ≤0.05 and an error factor <2. We have successfully quantified the increase of extracellular matrix components like aggrecan and other proteoglycans, and the decrease of degradative enzymes such as cathepsins, caused by the administration of CS. Annexins were increased by the drug while a glycolitic enzyme was decreased. Finally, we found altered several proteins involved in cell adhesion and angiogenesis; among them we observed a strong CS-dependent increase of an angiogenesis inhibitor, thrombospondin-1 (TSP1). Owing to the pivotal role of angiogenesis in OA physiopathology, we decided to verify TSP1 gene expression level in CS-treated chondrocytes by real time-PCR analysis. TSP1 protein level was also verified in chondrocyte conditioned media (secretome) and cellular extracts (proteome) by western blot analyses, and in cartilage explants by immunohistochemistry. Data obtained in the validation experiments confirmed those from proteomics. Conclusions: We have generated a quantitative profile of chondrocyte extracellular protein changes driven by CS in OA HACs using iTRAQ reagents. Although this study is limited to an in vitro system, demonstration of the anti-angiogenic action of CS might provide a novel therapeutic approach for OA targeting. Hopefully proteins modulated by CS, such as TSP-1, should be used in the next future as biomarkers for monitoring treatment efficacy and allowing early determination of responder and non-responder OA patients. References: Calamia V, et al. Arthritis Res Ther. 2010:R138. Calamia V, et al. Mol Cell Proteomics. 2011 Dec. Calamia V, et al. Arthritis Res Ther. 2012 Oct. Disclosure of Interest: V. Calamia: None Declared, L. Lourido: None Declared, J. Mateos: None Declared, P. Fernandez-Puente: None Declared, B. Rocha: None Declared, C. Fernandez-Costa: None Declared, E. Montell Employee of: Bioibérica, J. Vergés Employee of: Bioibérica, C. Ruiz-Romero: None Declared, F. Blanco: None Declared